Regenerative Revolution - Devon Blaskevitch (Journal of Innovation in Polytechnic Education)
Canada’s polytechnics have long been at the forefront of innovations in sustainability and combatting climate change. These institutions have the capacity to play a critical role in driving the adoption of climate-conscious practices throughout industry and the wider community. As the need to move past sustainability and propel the adoption of regenerative practices is better understood, polytechnics are uniquely positioned to drive this shift. This paper explores the concept of regenerative design and how Canada’s polytechnics have employed on-campus initiatives and infrastructure projects in three broad categories: production of excess energy, recycling and reusing waste or runoff, and ecological (re)integration. Through these endeavours, the institutions are positioning themselves as role models and intermediaries able to introduce and help stakeholders adopt regenerative practices. Maximizing this capacity is an important way the Government of Canada can achieve its climate-related objectives as laid out in the 2022 Federal Sustainable Development Strategy. By harnessing polytechnic regenerative expertise and their deep ties to both industry and their surrounding communities, Canada will be better positioned to meet its ambitious climate targets.